Multiomics approach reveals a role of translational machinery in shaping maize kernel amino acid composition. Issue 1 (15th August 2021) - Shrestha, Vivek; Yobi, Abou; Slaten, Marianne L; Chan, Yen On; Holden, Samuel; Gyawali, Abiskar; Flint-Garcia, Sherry; Lipka, Alexander E; Angelovici, Ruthie
Abstract: Maize ( Zea mays ) seeds are a good source of protein, despite being deficient in several essential amino acids. However, eliminating the highly abundant but poorly balanced seed storage proteins has revealed that the regulation of seed amino acids is complex and does not rely on only a handful of proteins. In this study, we used two complementary omics-based approaches to shed light on the genes and biological processes that underlie the regulation of seed amino acid composition. We first conducted a genome-wide association study to identify candidate genes involved in the natural variation of seed protein-bound amino acids. We then used weighted gene correlation network analysis to associate protein expression with seed amino acid composition dynamics during kernel development and maturation. We found that almost half of the proteome was significantly reduced during kernel development and maturation, including several translational machinery components such as ribosomal proteins, which strongly suggests translational reprogramming. The reduction was significantly associated with a decrease in several amino acids, including lysine and methionine, pointing to their role in shaping the seed amino acid composition. When we compared the candidate gene lists generated from both approaches, we found a nonrandom overlap of 80 genes. A functional analysis of these genes showed a tight interconnected cluster dominated by translational machinery genes, especially ribosomal proteins, further supporting the role of translation dynamics in shaping seed amino acid composition. These findings strongly suggest that seed biofortification strategies that target the translation machinery dynamics should be considered and explored further. Abstract : An integrated approach reveals the key role of translational machinery in maize kernel amino acid natural variation and homeostasis, highlighting targets for seed amino acid biofortification.